Site‐Directed and Global Incorporation of Orthogonal and Isostructural Noncanonical Amino Acids into the Ribosomal Lasso Peptide Capistruin. Issue 3 (11th December 2014) - Al Toma, Rashed S.; Kuthning, Anja; Exner, Matthias P.; Denisiuk, Alexander; Ziegler, Juliane; Budisa, Nediljko; Süssmuth, Roderich D.
Abstract Expansion of the structural diversity of peptide antibiotics was performed through two different methods. Supplementation‐based incorporation (SPI) and stop‐codon suppression (SCS) approaches were used for co‐translational incorporation of isostructural and orthogonal noncanonical amino acids (ncAAs) into the lasso peptide capistruin. Two ncAAs were employed for the SPI method and five for the SCS method; each of them probing the incorporation of ncAAs in strategic positions of the molecule. Evaluation of the assembly by HR‐ESI‐MS proved more successful for the SCS method. Bio‐orthogonal chemistry was used for post‐biosynthetic modification of capistruin congener Cap_Alk10 containing the ncAA Alk (Nε‐Alloc‐L‐lysine) instead of Ala. A second‐generation Hoveyda–Grubbs catalyst was used for an in vitro metathesis reaction with Cap_Alk10 and an allyl alcohol, which offers options for post‐biosynthetic modifications. The use of synthetic biology allows for the in vivo production of new peptide‐based antibiotics from an expanded amino acid repertoire.